ETHNOBIOPROSPECTING OF THE MALAY COMMUNITY IN LINGGA SUB-DISTRICT, LINGGA DISTRICT, RIAU ISLAND - Wulandari, Dwi Putri; Zuhud, Ervizal A.M.; Siswoyo, Siswoyo (Media Konservasi, 2023)
The life of the Malay community in Lingga District cannot be separated from the very close interaction with the natural resources around it, namely interactions related to the use of plants and animals. The knowledge of the Malay community in the Lingga sub-district in the use of plants and animals is important to be studied and documented so that the knowledge of the community can be sustainable for posterity. This study aimed to identify and describe the ethnobioprospecting of plant and animal species based on utilization by the Malay community in Lingga District. Data were collected using in-depth interviews, analysis of vegetation to determine the potential of plants, and field observations using exploratory surveys to determine the potential of animals. The number of plant species from the results of vegetation analysis in several forest ecosystems in Lingga District was obtained as many as 110 species from 60 families. The utilization of plants by the Malay community in the Lingga sub-district can be categorized into 11 categories with the most species, namely plants as food (111 species) with the most families, namely Fabaceae (36 species). The use of animals can be categorized into six categories, most of which are food sources. Thus, the utilization of plants and animals by the Malay Community in the Lingga Subdistrict has been fulfilled from their natural resources. Key words: animals, Malay society, plants, utilization